Model of delivery of cancer care in South Africa's Eastern Cape and Mpumalanga provinces: a situational analysis protocol. Issue 2 (1st February 2022) - Chitha, Wezile; Swartbooi, Buyiswa; Jafta, Zukiswa; Funani, Itumeleng; Maake, Kedibone; Hongoro, Danleen; Godlimpi, Lizo; Mnyaka, Onke R; Williams, Natasha; Buthi, Lazola; Kuseni, Sibulelo; Zungu, Christopher; et al.
Abstract : Introduction: Cancer contributes to a significant proportion of morbidity and mortality globally. Low-income and middle-income countries such as South Africa tend to be characterised by poor and inequitable access to cancer services. Cancer resources are more likely to be found in urban areas, tertiary centres and quaternary hospitals. However, little is known about the linkages to care, continuity of care and packages of cancer care in rural South African settings. This study describes cancer service delivery for South Africa's Eastern Cape and Mpumalanga provinces. Methods and analysis: A mixed-methods qualitative and quantitative research methods of three substudies which include semistructured interviews with patients, focus group discussions with health providers and a quantitative record review that will be carried out at both Rob Ferreira hospital, Witbank hospital and Nelson Mandela Academic hospital in Mpumalanga and Eastern Cape province, respectively. Instruments assess demographic characteristics, explore packages of cancer care, explore challenges experienced by health professionals, and maps out the referral pathway of patients with a cancer diagnosis in the study sites. Numerical, quantitative data will be explored for normality using the Shapiro-Wilk test and reported using either the mean, SD and range or the median and IQR depending on the normality of the distribution. Qualitative data will be analysed using the phenomenological approach. Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committee of Walter Sisulu University (040/2020) and the University of the Witwatersrand (M210211), South Africa. To the research team's knowledge, this is the first study presenting the model of cancer delivery in South Africa's Eastern Cape and Mpumalanga province. This will thus provide better understanding of cancer service delivery systems, packages of cancer care from primary care to quaternary care.